Жоғары сынып оқушыларын отбасы-некелік өмірге даярлаудың психологиялық-педагогикалық негіздері - Каирова, Б.К.; Молдахметова, Г.М. (My University, 2013)
The paper contains a theoretical and scientific analysis of the psychological-pedagogical ideas of foreign and local psychologists to study the problem. The paper contains a theoretical and scientific analysis of the psychological-pedagogical ideas of foreign and local psychologists to study the problem.